California Maritime Academy Triple Ceremonies - Pacific Marine Review (Pacific Marine Review)
Saturday, September 7 will long be remembered as one of rhe greatest days in the 16 years of the Academy's history. The triple-treat observance that day included the rechristening of the Training Ship Golden Bear followed by the dedication of the memorial gymnasium and completed by the graduation ceremonies of the class of September 1946.